2019
DOI: 10.1002/lary.28331
|View full text |Cite
|
Sign up to set email alerts
|

The minimal clinically important difference of the dyspnea index in laryngotracheal stenosis

Abstract: Objective The Dyspnea Index (DI) is a validated patient‐reported outcome (PRO) instrument that has been used in the management of laryngotracheal stenosis (LTS). The minimal clinically important difference (MCID) is an established concept to help determine the change in a PRO instrument that reflects meaningful change for the patient. It is not known what change in the DI is of clinical significance in airway surgery. This study aims to determine the MCID for the DI in patients undergoing surgical treatment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Gray et al recently cited the minimal clinically important difference in the DI to be 4 for patients with laryngotracheal stenosis undergoing airway surgery. 22 The observed mean change here of 5 would be just above that threshold, at least at short-term follow-up, though the specific minimal clinically important change in UVFP is unknown. For patients with baseline dyspnea or for whom an increase in dyspnea is a main concern, trial saline injection augmentation 23 or short-acting injection augmentation could be considered.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Gray et al recently cited the minimal clinically important difference in the DI to be 4 for patients with laryngotracheal stenosis undergoing airway surgery. 22 The observed mean change here of 5 would be just above that threshold, at least at short-term follow-up, though the specific minimal clinically important change in UVFP is unknown. For patients with baseline dyspnea or for whom an increase in dyspnea is a main concern, trial saline injection augmentation 23 or short-acting injection augmentation could be considered.…”
Section: Discussionmentioning
confidence: 74%
“…Importantly, only 6 of 43 patients had an increased DI score after intervention, with a change from 6 ± 9 to 11 ± 8. Gray et al recently cited the minimal clinically important difference in the DI to be 4 for patients with laryngotracheal stenosis undergoing airway surgery 22 . The observed mean change here of 5 would be just above that threshold, at least at short‐term follow‐up, though the specific minimal clinically important change in UVFP is unknown.…”
Section: Discussionmentioning
confidence: 89%
“…When serially following a patient, the change in DI score can discriminate between those experiencing a significant change in their level of dyspnea and those who do not (minimal clinically important difference of 4). 23 Clinically, however, we have observed a mismatch between the clinicianreported degree of stenosis and patients' DI scores. In order to better understand this, we set out to determine how well clinician-reported degree of stenosis predicted the variation in patients' reported degree of dyspnea.…”
Section: Introductionmentioning
confidence: 77%
“…Five studies (Table I and Table II, top) reported MCID of objective outcome measurements/tests (vestibuloocular reflex gain, 14 peak nasal expiratory flow, 15 peak nasal inspiratory flow, 15,16 Brief Smell Identification Test, 17 and laryngotracheal stenosis 18 ). In comparison, 30 studies reported 45 PROM MCID values (Table I and Table II, bottom) 19–48 . While all studies reported the MCID for improvement in an outcome, only five studies (17.2%) also reported an MCID for worsening in an outcome 24,33,39,41,45 …”
Section: Resultsmentioning
confidence: 99%